What makes health systems resilient? A qualitative analysis of the perspectives of Swiss NGOs - Pauline Yongeun Grimm; Kaspar Wyss (BMC, 2022)
Abstract Background Resilience has become relevant than ever before with the advent of increasing and intensifying shocks on the health system and its amplified effects due to globalization. Using the example of non-state actors based in Switzerland, the aim of this study is to explore how and to what extent NGOs with an interest in global health have dealt with unexpected shocks on the health systems of their partner countries and to reflect on the practical implications of resilience for the multiple actors involved. Consequently, this paper analyses the key attributes of resilience that targeted investments may influence, and the different roles key stakeholders may assume to build resilience. Methods This is a descriptive and exploratory qualitative study analysing the perspectives on health system resilience of Swiss-based NGOs through 20 in-depth interviews. Analysis proceeded using a data-driven thematic analysis closely following the framework method. An analytical framework was developed and applied systematically resulting in a complete framework matrix. The results are categorised into the expected role of the governments, the role of the NGOs, and practical future steps for building health system resilience. Results The following four key 'foundations of resilience' were found to be dominant for unleashing greater resilience attributes regardless of the nature of shocks: 'realigned relationships,' 'foresight,' 'motivation,' and 'emergency preparedness.' The attribute to 'integrate' was shown to be one of the most crucial characteristics of resilience expected of the national governments from the NGOs, which points to the heightened role of governance. Meanwhile, as a key stakeholder group that is becoming inevitably more powerful in international development cooperation and global health governance, non-state actors namely the NGOs saw themselves in a unique position to facilitate knowledge exchange and to support long-term adaptations of innovative solutions that are increasing in demand. The strongest determinant of resilience in the health system was the degree of investments made for building long-term infrastructures and human resource development which are well-functioning prior to any potential crisis. Conclusions Health system resilience is a collective endeavour and a result of many stakeholders' consistent and targeted investments. These investments open up new opportunities to seek innovative solutions and to keep diverse actors in global health accountable. The experiences and perspectives of Swiss NGOs in this article highlight the vital role NGOs may play in building resilient health systems in their partner countries. Specifically, strong governance, a bi-directional knowledge exchange, and the focus on leveraging science for impact can draw greater potential of resilience in the health systems. Governments and the NGOs have unique points of contribution in this journey towards resilience and bear the responsibility to support governments to prioritise investing in the key 'foundations of resilience' in order to activate greater attributes of resilience. Resilience building will not only prepare countries for future shocks but bridge the disparate health and development agenda in order to better address the nexus between humanitarian aid and development cooperation.